Thermus aquaticus: Keunikan Genetik dan Perannya dalam Revolusi PCR melalui Taq Polymerase - Tenri Ampa Nurfitria Papada, Andi; Astuti S, Dewi; Hala, Yusminah (Universitas PGRI Adi Buana Surabaya, 2025)
Thermus aquaticus is a thermophilic bacterium known for its ability to produce thermostable enzymes, such as Taq polymerase, which plays an important role in the Polymerase Chain Reaction (PCR) technique. This study aims to examine the characteristics, ecology, and potential applications of thermostable enzymes produced by this bacterium in various industrial and biotechnological fields. The study was conducted through a literature review using a search method in scientific databases such as PubMed, Scopus, and Google Scholar. The results of the study showed that T. aquaticus has an optimal growth temperature between 70-75°C and is found in extreme environments such as hot springs and hydrothermal systems. Its characteristics, which include strong cell walls, unique membrane lipid content, and thermostable enzymes, allow this bacterium to survive in high temperature conditions. The Taq polymerase enzyme isolated from this bacterium has revolutionized the field of biotechnology, especially in PCR which is used for DNA amplification in genetics, medicine, and forensics research. In addition to PCR, thermostable enzymes from T. aquaticus have wide applications in the food, pharmaceutical, and bioremediation industries. Its existence in the ecosystem shows an important role in the biogeochemical cycle and its interaction with other microorganisms in extreme environments. This finding confirms that the exploration of extremophile microorganisms, including T. aquaticus, still has great potential in technological innovation and the development of biotechnology-based industries.